Condition of Families Receiving Social Assistance to Persons With Severe Disabilities - Ruaida Murni; Mulia Astuti (Jurnal Penelitian Kesejahteraan Sosial, 2017)
This study is aimed to comprehend the condition of families receiving severe disability social assistant program (ASPDB), which is seen from the economy aspect and family competence aspect in caring for persons with severe disabilities (PDB). Data and information were collected through interviews with families of persons with disabilities, through the observation of the condition of persons with disabilities (PDB) and their families concerned and also through study of documentations. The research was conducted in Padang city and the results showed that the families economic condition of the persons with severe disabilities (PDB) generally made a living with income below Padang city regional minimum wage, which was obtained from permanent jobs and additional jobs. But within this condition, families of PDB said thatthey were able to fulfill the needs of persons with severe disabilities (PDB), although it still fulfilled at minimal needs as what it is. The families of persons with severe disabilities did not precisely know the specific need of persons with severe disabilities, even once there was a respondent who said that the needs of persons with severe disabilities are merely the sameas that of normal people. The families of persons with severe disabilities know where to do the therapy, but the majority of persons with severe disabilities are not given therapy as one of the health care needs under certain reasons as follow: persons with severe disabilities have already been mature, it is difficult to take them to the therapist, and no improvementseen though undergoing therapy.The way the families bring the persons with severe disabilities taking shower reflects that the families concerned have not possessed sufficient knowledge of how to bathe them in accordance with their disabilities. Most of families have never felt disappointed or upset with the condition of their disabilities. Based on the research, it is recommended that families concerned need to enhance the knowledge and skills in providing care and services to persons with severe disabilities.